2012
DOI: 10.1002/jbm.a.34224
|View full text |Cite
|
Sign up to set email alerts
|

Suture pullout strength and in vitro fibroblast and RAW 264.7 monocyte biocompatibility of genipin crosslinked nanofibrous chitosan mats for guided tissue regeneration

Abstract: Guided tissue regeneration (GTR) is a surgical technique used to direct the formation of bone in the graft space by protecting it with a barrier membrane used to exclude soft tissues during healing. Chitosan has been advocated for GTR applications because of its biocompatibility, degradability, wound healing, and osteogenic properties. In this study, electrospun chitosan membranes, crosslinked with 5 mM or 10 mM geinipin, a natural crosslinker extracted from the gardenia plant, were evaluated for suture pullou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 37 publications
3
62
0
Order By: Relevance
“…Moreover, the GP-crosslinked tissue had an impressive mechanical strength and resistance against in vitro enzymatic degradation compared to the GTA-crosslinked tissues (Sung, Huang, Huang, Tsai, & Chiu, 1998). However, although crosslinking CTS with GP has been proposed to be a better replacement for GTA to prepare CTS scaffolds with improved performance for some years (Mi, Tan, Liang, Huang, & Sung, 2001), this approach was attempted only recently for crosslinking CTS in the nanofibrous form (Austero, Donius, Wegst, & Schauer, 2012;Bavariya et al, 2014;Frohbergh et al, 2012;Norowski, Mishra, Adatrow, Haggard, & Bumgardner, 2012). With different crosslinking procedures performed, varied results were obtained with poor comparability.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the GP-crosslinked tissue had an impressive mechanical strength and resistance against in vitro enzymatic degradation compared to the GTA-crosslinked tissues (Sung, Huang, Huang, Tsai, & Chiu, 1998). However, although crosslinking CTS with GP has been proposed to be a better replacement for GTA to prepare CTS scaffolds with improved performance for some years (Mi, Tan, Liang, Huang, & Sung, 2001), this approach was attempted only recently for crosslinking CTS in the nanofibrous form (Austero, Donius, Wegst, & Schauer, 2012;Bavariya et al, 2014;Frohbergh et al, 2012;Norowski, Mishra, Adatrow, Haggard, & Bumgardner, 2012). With different crosslinking procedures performed, varied results were obtained with poor comparability.…”
Section: Introductionmentioning
confidence: 87%
“…To cater for tissue engineering uses, in situ crosslinking (Austero et al, 2012;Norowski et al, 2012) or post-electrospinning crosslinking treatment (Frohbergh et al, 2012) may be performed to inhibit solvability and improve mechanical properties of the as-electrospun CTS nanofibers. In this study, a post-electrospinning crosslinking with the naturally occurring crosslinker GP was proceeded to chemically crosslink the electrospun CTS nanofibers, and the commonly used crosslinker GTA was used as control.…”
Section: Crosslinking Of the Electrospun Cts Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…An injection volume of 50 mL and a specific refractive index increment (dn/dc) for chitosan of 0.163 mL/g were used. 22 Crystallinity X-ray diffraction (XRD) was used to characterize the crystal structure of the raw chitosan material, as well as neutral, 4.6 pH, and 5.6 pH buffered chitosan sponges. XRD patterns were determined using multiple scans from a Bruker AXS (Madison, WI) Advanced D8 X-ray diffractometer with Ka Cu radiation source at 40 kV and 40 mA over a 2h range from 5 to 40 with a step size of 0.05 and a time/step of 0.2 s.…”
Section: Molecular Weightmentioning
confidence: 99%
“…We have also demonstrated that the genipin crosslinked chitosan membranes were not cytotoxic to osteoblast or fibroblast cells, and did not cause monocyte activation. We have also shown the ability of genipin crosslinked electropun chitosan membranes to inhibit the LPS-induced release of nitric oxide (NO) from RAW 264.7 monocyte cells over a 3 day period [10]. NO expression is elevated in the periodontal and gingival tissues of patients with periodontitis and its inhibition is a potential therapeutic target [11,12].…”
Section: Introductionmentioning
confidence: 99%